Method for preparing light boron carbide ceramic by using coconut shell as raw material
By using coconut shell to produce boron carbide ceramics through carbonization and gel formation, the method addresses the inefficiencies of high-temperature synthesis, achieving lightweight boron carbide ceramics with high purity and controlled density.
Patent Information
- Application Number
- CN202411397120.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-09
AI Technical Summary
Existing methods for synthesizing boron carbide ceramics require high temperatures and are difficult to control the structure and density of lightweight boron carbide, leading to inefficient and complex processes.
A method using coconut shell as a raw material, involving carbonization, mixing with boric acid and tris(hydroxymethyl)aminomethane, gel formation, drying, and sintering under inert gas protection to produce lightweight boron carbide ceramics with controlled porosity and density.
The method simplifies the preparation process, enhances efficiency, and achieves lightweight boron carbide ceramics with high purity and controlled density, overcoming the limitations of traditional methods.
Smart Images

Figure CN119241272A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of boron carbide ceramic preparation, and particularly relates to a method for preparing lightweight boron carbide ceramic using coconut shell as a raw material. Background Art
[0002] Boron carbide, with the chemical formula B4C, has a low density (about 2.5g / cm 3 ), high strength and good physical and chemical stability, and has important applications in the fields of wear-resistant coatings and reactive armor, while its good neutron absorption properties make it valuable in the field of controlled nuclear fusion. In view of this, the preparation technology of high-quality boron carbide has always attracted attention.
[0003] The main methods for synthesizing boron carbide include direct synthesis using high-temperature reaction of carbon powder and boron powder, electric furnace (or carbon thermal) reduction using carbon to reduce B2O3 or boric acid, high-temperature self-propagating synthesis with the addition of magnesium powder, sol-gel method, chemical vapor deposition method, etc. However, both direct synthesis and reduction methods need to be carried out at high temperatures above 1800°C, and the synthesis temperature of boron carbide ceramics is generally higher than 2200°C. Even if sintering aids (such as SiO2, Al2O3, etc.) are added, the sintering temperature must be higher than 2000°C. The temperature conditions have high requirements for sintering equipment; the high-temperature self-propagating synthesis method has the problem of difficult removal of magnesium residues; although the sol-gel method can achieve relatively low temperature (1200-1500°C) preparation, the method of calcining synthesis under vacuum conditions with citric acid-boric acid as precursor has low production efficiency and complex process. On the other hand, due to its harsh preparation conditions, lightweight boron carbide is mainly synthesized by the method of "synthesis first, then pore creation", which makes it very difficult to control the structure and density of the pores. Summary of the invention
[0004] In order to solve the problems of difficult preparation, high preparation temperature and difficulty in lightweighting of boron carbide ceramics proposed in the background art, the present invention provides a method for preparing lightweight boron carbide ceramics using coconut shell as raw material.
[0005] The technical solution of the present invention is as follows:
[0006] The present invention provides a method for preparing lightweight boron carbide ceramics using coconut shell as raw material, comprising the following steps:
[0007] (1) After the coconut shell is carbonized under anaerobic conditions, it is crushed, ground and sieved to obtain carbon powder;
[0008] (2) mixing carbon powder, boric acid and tris(hydroxymethyl)aminomethane in deionized water and stirring in a constant temperature water bath to obtain a gel;
[0009] (3) After the gel is dried, it is ground and pressed to obtain a green body;
[0010] (4) The green body is sintered under the protection of an inert gas to obtain boron carbide ceramics.
[0011] The method for preparing lightweight boron carbide ceramics using coconut shell as raw material as described above, wherein in step (1), the carbonization temperature is 500-900° C. and the time is 3-5 hours;
[0012] In the step (2), the molar ratio of carbon powder to boric acid is 1:0.5-5, and the molar ratio of tris(hydroxymethyl)aminomethane to the mixture of carbon powder and boric acid is 1:0.2-2, which are mixed in 150 mL of deionized water;
[0013] In the sintering step (4), the heating rate is 2-15°C / min, the holding temperature is 1600-2000°C, and the holding time is 1-10h.
[0014] The method for preparing lightweight boron carbide ceramics using coconut shell as raw material as described above, wherein in step (1), the carbonization temperature is 600-900° C. and the time is 4.5-5 h;
[0015] In the step (2), the molar ratio of carbon powder to boric acid is 1:2-4, and the molar ratio of tris(hydroxymethyl)aminomethane to the mixture of carbon powder and boric acid is 1:0.2-1;
[0016] In the sintering step (4), the heating rate is 8-10°C / min, the holding temperature is 1700-1900°C, and the holding time is 4-8h.
[0017] In the step (1), the particle size of the carbon powder is 50-300 mesh.
[0018] In the step (2), the water bath temperature is 80-90° C. and the stirring time is 5-7 h.
[0019] In the step (3), the drying temperature is 100 to 250° C. and the drying time is 3 to 5 hours.
[0020] In the step (4), the density of the boron carbide ceramic is 1.53-1.81 g / cm 3 , boron carbide content is greater than 88%.
[0021] Beneficial Effects
[0022] The present invention uses coconut shell as raw material, obtains carbon powder through high-temperature carbonization, crushing, grinding and sieving, fully evaporates and cross-links a uniform mixture of carbon powder, boric acid and tris(hydroxymethyl)aminomethane to obtain gel, converts the gel into precursor powder by combustion method, and finally obtains porous boron carbide ceramics through dry pressing and high-temperature sintering, realizes the integration of the two-step process of boron carbide powder preparation and pore formation, effectively simplifies the preparation process of lightweight boron carbide ceramics and improves efficiency.
[0023] The invention realizes controllable adjustment of gelation speed, boron carbide generation amount and porosity by controlling the molar ratio of carbon powder to boric acid and the addition amount of trishydroxymethylaminomethane.
[0024] The present invention selects trishydroxymethylaminomethane as a chelating agent and a pore-forming agent, does not need to add auxiliary agents, does not generate by-products, has high purity of the obtained product, does not need to add additional reagents to control the pH value, and has a simple and easy process. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the X-ray diffraction (XRD) pattern of the boron carbide ceramic prepared in Example 1 of the present invention.
[0026] Figure 2 This is the X-ray diffraction (XRD) pattern of the boron carbide ceramic prepared in Comparative Example 3 of the present invention.
[0027] Figure 3 This is a scanning electron microscope (SEM) photograph of the boron carbide ceramic prepared in Example 1 of the present invention.
[0028] Figure 4 This is a scanning electron microscope (SEM) photograph of the boron carbide ceramic prepared in Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0029] The following examples are intended to illustrate the present invention rather than to further limit the present invention.
[0030] The present invention provides a method for preparing lightweight boron carbide ceramics using coconut shell as raw material, comprising the following steps:
[0031] (1) After coconut shells are carbonized under anaerobic conditions, they are crushed, ground, and sieved to obtain carbon powder.
[0032] Using biomass coconut shell as carbon source, coconut shell has extremely high carbon content (>90%), which is an ideal carbon source. Moreover, using coconut shell as carbon source can realize the effective utilization of coconut shell waste, which is green and environmentally friendly.
[0033] In order to achieve complete carbonization of coconut shells, the carbonization temperature and time of coconut shells need to be reasonably controlled. Preferably, the carbonization temperature is 500-900°C and the time is 3-5h; more preferably, the carbonization temperature is 600-900°C and the time is 4.5-5h.
[0034] After carbonization, block-shaped aggregated carbon is obtained, and the obtained block-shaped aggregated carbon is crushed, ground and sieved to obtain micron-sized carbon powder. Preferably, the particle size of the carbon powder is 50-300 meshes, so as to facilitate uniform mixing with boric acid and tris(hydroxymethyl)aminomethane in subsequent processes.
[0035] (2) Carbon powder, boric acid and tris(hydroxymethyl)aminomethane are mixed in deionized water and stirred in a constant temperature water bath to obtain a gel.
[0036] Preferably, the molar ratio of carbon powder to boric acid is 1:0.5-5, and the molar ratio of tris(hydroxymethyl)aminomethane to the mixture of carbon powder and boric acid is 1:0.2-2, and they are mixed in 150 mL of deionized water.
[0037] More preferably, the molar ratio of carbon powder to boric acid is 1:2-4, and the molar ratio of tris(hydroxymethyl)aminomethane to the mixture of carbon powder and boric acid is 1:0.2-1.
[0038] The invention realizes controllable adjustment of gelation speed, boron carbide generation amount and porosity by controlling the molar ratio of carbon powder to boric acid and the addition amount of trishydroxymethylaminomethane.
[0039] In addition, during the gelation process, the water bath temperature is 80-90°C and the stirring time is 5-7h.
[0040] The present invention selects trishydroxymethylaminomethane as a chelating agent and a pore-forming agent, does not need to add auxiliary agents, does not generate by-products, has high purity of the obtained product, does not need to add additional reagents to control the pH value, and has a simple and easy process.
[0041] (3) After the gel is dried, it is ground and pressed to obtain a green body.
[0042] Preferably, the drying temperature is 100-250° C. and the drying time is 3-5 hours. The present invention selects tris(hydroxymethyl)aminomethane as a chelating agent and a pore-forming agent, and by controlling the drying temperature and performing a combustion reaction, the precursor powder can be generated and the tris(hydroxymethyl)aminomethane can be retained to play a pore-forming role.
[0043] The obtained precursor powder is ground, dry-pressed and pressed into a ceramic body.
[0044] (4) The green body is sintered under the protection of an inert gas to obtain boron carbide ceramics.
[0045] High temperature sintering is achieved by programmed temperature increase. Preferably, the heating rate is 2 to 15°C / min, the holding temperature is 1600 to 2000°C, and the holding time is 1 to 10 hours.
[0046] More preferably, the heating rate is 8-10°C / min, the holding temperature is 1700-1900°C, and the holding time is 4-8h.
[0047] The present invention ensures high-abundance generation of boron carbide by controlling the heating rate, the holding temperature and the time, and realizes the regulation of the pore structure / density.
[0048] The boron carbide ceramics obtained by the method of the present invention have a density of 1.53-1.81 g / cm 3 , and the boron carbide content is greater than 88%. Not only is the density low, but the purity is also high.
[0049] The present invention uses coconut shell as raw material, obtains carbon powder through high-temperature carbonization, crushing, grinding and sieving, fully evaporates and cross-links a uniform mixture of carbon powder, boric acid and tris(hydroxymethyl)aminomethane to obtain gel, converts the gel into precursor powder by combustion method, and finally obtains porous boron carbide ceramics through dry pressing and high-temperature sintering, realizes the integration of the two-step process of boron carbide powder preparation and pore formation, effectively simplifies the preparation process of lightweight boron carbide ceramics and improves efficiency.
[0050] Example 1
[0051] (1) placing coconut shells in a high-temperature box furnace, keeping the temperature at 600° C. for 5 h under closed oxygen-free conditions to completely carbonize the coconut shells to obtain block-shaped aggregated carbon, crushing and grinding the obtained block-shaped aggregated carbon into carbon powder, and passing through a 100-mesh sieve to obtain micron-sized carbon powder;
[0052] (2) carbon powder and boric acid are mixed in 150 mL of deionized water at a molar ratio of 1:4, and tris(hydroxymethyl)aminomethane is added at a molar ratio of 1:0.5 to the mixture of carbon powder and boric acid, and stirred for 5 h in a 90° C. constant temperature water bath under magnetic stirring, and mixed evenly, and cross-linked to obtain a viscous gel after sufficient evaporation;
[0053] (3) The gel is placed in a drying oven and dried at 180° C. for 4 h to obtain a precursor powder; the precursor powder is ground and dry-pressed to form a ceramic body.
[0054] (4) The green body is placed in an argon-protected tubular furnace, heated to 1800°C at a rate of 8°C / min and kept at that temperature for 4 hours for sintering to obtain boron carbide ceramics.
[0055] Example 2
[0056] (1) placing coconut shells in a high-temperature box furnace, keeping the temperature at 800° C. for 4.5 h under closed oxygen-free conditions to completely carbonize the coconut shells to obtain block-shaped aggregated carbon, crushing and grinding the obtained block-shaped aggregated carbon into carbon powder, and passing the carbon powder through a 50-mesh sieve to obtain micron-sized carbon powder;
[0057] (2) carbon powder and boric acid are mixed in 150 mL of deionized water at a molar ratio of 1:5, and tris(hydroxymethyl)aminomethane is added at a molar ratio of 1:0.2 to the mixture of carbon powder and boric acid, and stirred in a 90° C. constant temperature water bath with magnetic stirring for 7 h to mix evenly, and cross-linked to obtain a viscous gel after sufficient evaporation;
[0058] (3) The gel is placed in a drying oven and dried at 100° C. for 5 h to obtain a precursor powder; the precursor powder is ground and dry-pressed to form a ceramic body.
[0059] (4) The green body is placed in an argon-protected tubular furnace, heated to 1700°C at a rate of 10°C / min and kept at that temperature for 8 hours for sintering to obtain boron carbide ceramics.
[0060] Example 3
[0061] (1) placing coconut shells in a high-temperature box furnace, keeping the temperature at 500° C. for 3 h under closed oxygen-free conditions to completely carbonize the coconut shells to obtain block-shaped aggregated carbon, crushing and grinding the obtained block-shaped aggregated carbon into carbon powder, and passing through a 200-mesh sieve to obtain micron-sized carbon powder;
[0062] (2) mixing carbon powder and boric acid in a molar ratio of 1:0.5 in 150 mL of deionized water, and then adding tris(hydroxymethyl)aminomethane in a molar ratio of 1:2 to the mixture of carbon powder and boric acid, stirring for 6 h in a constant temperature water bath at 80° C. and under magnetic stirring, mixing evenly, and cross-linking after sufficient evaporation to obtain a viscous gel;
[0063] (3) The gel is placed in a drying oven and dried at 250° C. for 3 h to obtain a precursor powder; the precursor powder is ground and dry-pressed to form a ceramic body.
[0064] (4) The green body is placed in an argon-protected tubular furnace, heated to 1600°C at a rate of 2°C / min and kept at this temperature for 10 h for sintering to obtain boron carbide ceramics.
[0065] Example 4
[0066] (1) placing coconut shells in a high-temperature box furnace, keeping the temperature at 900° C. for 4.5 h under closed oxygen-free conditions to completely carbonize the coconut shells to obtain block-shaped aggregated carbon, crushing and grinding the obtained block-shaped aggregated carbon into carbon powder, and passing through a 300-mesh sieve to obtain micron-sized carbon powder;
[0067] (2) mixing carbon powder and boric acid in a molar ratio of 1:2 in 150 mL of deionized water, and then adding tris(hydroxymethyl)aminomethane in a molar ratio of 1:1 to the mixture of carbon powder and boric acid, stirring for 5 h in a constant temperature water bath at 85° C. and under magnetic stirring, mixing evenly, and cross-linking after sufficient evaporation to obtain a viscous gel;
[0068] (3) The gel is placed in a drying oven and dried at 180° C. for 3 h to obtain a precursor powder; the precursor powder is ground and dry-pressed to form a ceramic body.
[0069] (4) The green body is placed in an argon-protected tubular furnace, heated to 2000°C at a rate of 15°C / min and kept at that temperature for 1 hour for sintering to obtain boron carbide ceramics.
[0070] Comparative Example 1
[0071] Compared with Example 1, sintering is performed at 1300° C. in step (4), and the other operations remain unchanged.
[0072] Comparative Example 2
[0073] Compared with Example 1, the carbonization temperature used in step (1) is 400° C., and the other operations remain unchanged.
[0074] Comparative Example 3
[0075] (1) placing coconut shells in a high-temperature box furnace, keeping the temperature at 600° C. for 5 h under closed oxygen-free conditions to completely carbonize the coconut shells to obtain block-shaped aggregated carbon, crushing and grinding the obtained block-shaped aggregated carbon into carbon powder, and passing through a 100-mesh sieve to obtain micron-sized carbon powder;
[0076] (2) carbon powder and boric acid are mixed in 150 mL of deionized water at a molar ratio of 1:4, and then citric acid is added at a molar ratio of 1:0.5 to the mixture of carbon powder and boric acid, and stirred for 5 h in a 90°C constant temperature water bath under magnetic stirring conditions to mix evenly, and the pH value of the mixture is adjusted to 3-4 with concentrated ammonia water, and a viscous gel is obtained after sufficient evaporation and cross-linking;
[0077] (3) The gel is placed in a drying oven and dried at 180° C. for 4 h to obtain a precursor powder; the precursor powder is ground and dry-pressed to form a ceramic body.
[0078] (4) The green body is placed in an argon-protected tubular furnace, heated to 1800°C at a rate of 8°C / min and kept at that temperature for 4 hours for sintering to obtain boron carbide ceramics.
[0079] Experimental Results
[0080] 1. Phase analysis
[0081] The boron carbide ceramics prepared in Examples 1-4 and Comparative Examples 1-3 were subjected to phase analysis by X-ray diffraction (XRD). Figure 1 , Figure 2 The X-ray diffraction (XRD) patterns of the boron carbide ceramics prepared in Example 1 and Comparative Example 3, respectively.
[0082] Depend on Figure 1 It can be seen that the boron carbide ceramic prepared in Example 1 has a higher boron carbide content;
[0083] Depend on Figure 2 It can be seen that the boron carbide ceramic prepared in Comparative Example 3 contains a large amount of free carbon and the amount of boron carbide generated is low.
[0084] Therefore, the boron carbide ceramic prepared by the method of the present application has a high boron carbide content and high purity.
[0085] 2. Morphology Analysis
[0086] The boron carbide ceramics prepared in Examples 1-4 and Comparative Examples 1-3 were subjected to morphological analysis using a scanning electron microscope (SEM). Figure 3 ) contains a large number of pores, while the boron carbide ceramics prepared in Comparative Example 3 ( Figure 4 ) contains a small amount of pores.
[0087] 3. Comparison results
[0088] The density and boron carbide content of the boron carbide ceramics prepared in Examples 1-4 and Comparative Examples 1-3 are compared, as shown in Table 1.
[0089] Table 1 Comparison of density and boron carbide content of different porous boron carbide ceramics
[0090]
[0091] As shown in Table 1, compared with Comparative Examples 1-3, the boron carbide ceramics obtained by the method of the present invention have a density of 1.53-1.81 g / cm 3 , and the boron carbide content is greater than 88%. Not only is the density low, but the purity is also high.
Claims
1. A method for preparing lightweight boron carbide ceramics using coconut shell as raw material, characterized in that: The following steps are involved: (1) After the coconut shell is carbonized under anaerobic conditions, it is crushed, ground and sieved to obtain carbon powder; (2) mixing carbon powder, boric acid and tris(hydroxymethyl)aminomethane in deionized water and stirring in a constant temperature water bath to obtain a gel; (3) After the gel is dried, it is ground and pressed to obtain a green body; (4) The green body is sintered under the protection of an inert gas to obtain boron carbide ceramics.
2. The method for preparing lightweight boron carbide ceramics using coconut shell as raw material according to claim 1, characterized in that: In the step (1), the carbonization temperature is 500-900° C. and the time is 3-5 hours; In the step (2), the molar ratio of carbon powder to boric acid is 1:0.5-5, and the molar ratio of tris(hydroxymethyl)aminomethane to the mixture of carbon powder and boric acid is 1:0.2-2, which are mixed in 150 mL of deionized water; In the sintering step (4), the heating rate is 2-15°C / min, the holding temperature is 1600-2000°C, and the holding time is 1-10h.
3. The method for preparing lightweight boron carbide ceramics using coconut shell as raw material according to claim 2, characterized in that: In the step (1), the carbonization temperature is 600-900° C. and the time is 4.5-5 h; In the step (2), the molar ratio of carbon powder to boric acid is 1:2-4, and the molar ratio of tris(hydroxymethyl)aminomethane to the mixture of carbon powder and boric acid is 1:0.2-1; In the sintering step (4), the heating rate is 8-10°C / min, the holding temperature is 1700-1900°C, and the holding time is 4-8h.
4. The method for preparing lightweight boron carbide ceramics using coconut shell as raw material according to claim 1, characterized in that: In the step (1), the particle size of the carbon powder is 50-300 mesh.
5. The method for preparing lightweight boron carbide ceramics using coconut shell as raw material according to claim 1, characterized in that: In the step (2), the water bath temperature is 80-90° C. and the stirring time is 5-7 h.
6. The method for preparing lightweight boron carbide ceramics using coconut shell as raw material according to claim 1, characterized in that: In the step (3), the drying temperature is 100 to 250° C. and the drying time is 3 to 5 hours.
7. The method for preparing lightweight boron carbide ceramics using coconut shell as raw material according to claim 1, characterized in that: In the step (4), the density of the boron carbide ceramic is 1.53-1.81 g / cm 3 , boron carbide content is greater than 88%.
Citation Information
Patent Citations
Method for fast preparing boron carbide ceramic powder
CN102731110A
Method for efficiently preparing nano boron carbide powder
CN112919474A
Method for rapidly producing spheroidic boron carbide ceramic powder
CN115594506A
Process for producing shaped bodies of boron carbide
DE3711871A1
Sintered boron carbide ceramic bodies
FR2723082A1
Cited By
Superconducting Ketjen black / boron carbide composite ceramic and preparation method and application thereof
CN119977582A
Preparation method of low-cost boron carbide powder and ceramic
CN121426567A
